CONFLICT MANAGEMENT AS THE EFFORT OF ACCOMPLISHING REPORT TOWARD MALADMINISTRATION OF THE POPULATION - I Gede Eko Putra Sri Sentanu; Mohammad Alifvigo Reicoba; Irwan Noor (DIA: Jurnal Administrasi Publik, 2020)
East Java is one of the regions that have the highest population maladministration reports in Indonesia. In 2017-2018, the Indonesian Ombudsman Representative Office in East Java experienced an increase in maladministration reports. This case caused many complaints from the public regarding the slow progress of population administration and led to internal and external conflicts of employees. This study aims to describe the function and role of the Indonesian Ombudsman Representative of East Java, the report completion process, and the strategy to overcome maladministration reports. This study employs a qualitative case study approach and is supported by the analysis using Atlas.ti software. Data collection is conducted through interviews, observation, and documentation. The findings reveal the role and function of the Indonesian Ombudsman Representative in East Java in terms of their effort to eradicate maladministration. Conflict management using progressive and participative methods (PROPARTIVE) is carried out for the completion of maladministration reports. PROPARTIVE methods explore the objectives of the reporter as a family to be open and mediate all parties to find solutions. The obstacles experienced by the Ombudsman in eradicating maladministration are the limited number of employees, the disobedience of the compliance with competencies, and the uncooperative reports between the reporter and the reported parties. Meanwhile, the supporting factors are the strategic location of the Indonesian Ombudsman Representative Office in East Java, the cooperation between employees and institutions, and the support of the Ombudsman website to facilitate the management of reports